Victory or defeat - How movement strategies destinguish fast direction changes from cutting maneuvers with high injury risk - David, S.; Peters, M.; Komnik, I.; Potthast, W. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Cutting maneuvers (CM) are frequently executed in sports. This task is relevant as it is a key ability by team sport players (TSP) but also bears the rlsk d ACL tears. An analysis of the movement strategies (MS) and musculoskeletal loads (MSL) occurring during CMs could reveal factors for efficient CMs and major triggers governing the occurrence of ACL tears. This study investigated the MS and MSL during 90" CMs in 51 subjects with different sex and sportive bacbround to analyze the variety of CM execution. Results indicate that sportive background and sex influences movement execution and MSL. Track and field athletes (TFA) had the same peak velocity as TSP, but produced it during the first step after the turn, whilst TSP kept speed by increased curve leaning. Females show higher knee adduction moments which increases the risk of injuries.